Ender’s Nail fixation in paediatric femoral shaft fractures. - Rajeev Dwivedi; S Shah; P Acharya; S Gurung (Journal of Lumbini Medical College, 2013)
Introduction: Femoral shaft fractures are among the most common major pediatric injuries treated by orthopaedic surgeons. Treatment ranges from strictly nonsurgical methods to surgical stabilization. Operative treatment of femoral shaft fractures in children with intramedullary nails (Ender’s and titanium elastic nails) is increasing because it has advantage of early mobilization, rapid healing and better control of alignment. Objectives: We evaluated the results of Ender’s nails fixation in femoral shaft fractures in children. Method: We studied 40 children with 40 femoral shaft fractures in age group 5-15 years. There were twenty four fractures in middle third, 7 in distal third and 9 in proximal third. Twenty fractures were transverse, 8 were oblique and 6 were spiral. Communition was seen in 6 cases. They were treated by closed reduction and Ender’s nail fixation. Retrograde fixation was done in 38 cases, in 2 cases antegrade fixation was done. Result: The mean follow up was 7.5 months. The average time to partial weight bearing was 3.8 weeks (2 to 6wks). The average time to full weight bearing was 8 weeks (6 to 12 wks). Union was achieved in all patients within a mean of 11 weeks (8 to 16 wks). Two patients had varus angulation of 8° and 6° each, whereas one had valgus angulation of 8°and one had anterior angulations of 10°. Lengthening of 1.2 cm was observed in one patient. In one case skin irritation due to nail was observed and that subsided without intervention. According to the Flynn criteria 34 had excellent and 6 had satisfactory results. No poor results were seen. Conclusion: Ender’s nail fixation can be preferred method of treatment for femoral shaft fractures in age group 5 -15 years as the results are excellent and satisfactory. It is technically simple and can be done in a closed manner. It spares the vascularity and growth plate.